The effects of an 8-week mindful eating intervention on anticipatory reward responses in striatum and midbrain - Janssen, Lieneke K.; Duif, Iris; Speckens, Anne E. M.; van Loon, Ilke; Wegman, Joost; de Vries, Jeanne H. M.; Cools, Roshan; Aarts, Esther (Frontiers in Nutrition, 2023)
Accumulating evidence suggests that increased neural responses during the anticipation of highcalorie food play an important role in the tendency to overeat. A promising method for counteracting enhanced food anticipation in overeating might be mindfulness-based interventions (MBIs). However, the neural mechanisms by which MBIs can affect food reward anticipation are unclear. In this randomized, actively controlled study, the primary objective was to investigate the effect of an 8-week mindful eating intervention on reward anticipation. We hypothesized that mindful eating would decrease striatal reward anticipation responses. Additionally, responses in the midbrain -from which the reward pathways originate -were explored. Using functional magnetic resonance imaging (fMRI), we tested 58 healthy participants with a wide body mass index range (BMI: 19-35 kg/m 2 ), motivated to change their eating behavior. During scanning they performed an incentive delay task, measuring neural reward anticipation responses to caloric and monetary cues before and after 8 weeks of mindful eating or educational cooking (active control). Compared with the educational cooking intervention, mindful eating affected neural reward anticipation responses, with reduced caloric relative to monetary reward responses. This effect was, however, not seen in the striatum, but only in the midbrain. The secondary objective was to assess temporary and long-lasting (one year follow-up) intervention effects on self-reported eating behavior and anthropometric measures (BMI, waist circumference, waist-to-hip-ratio (WHR)). We did not observe effects of the mindful eating intervention on eating behavior. Instead, the control intervention showed temporary beneficial effects on BMI, waist circumference, and diet quality, but not on WHR or self-reported eating behavior, as well as long-lasting increases in knowledge about healthy eating. These results suggest that an 8-week mindful eating intervention may have decreased the relative salience of food cues by affecting midbrain but not striatal reward responses, without necessarily affecting regular eating behavior. However, these exploratory results should be verified in confirmatory research. The primary and secondary objectives of the study were registered in the Dutch Trial Register (NTR): NL4923 (NTR5025).